Determinants of Economic Growth in 4 ASEAN Countries - Febryani, Tafeta; Kusreni, Sri (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2017)
Economic growth is a very important indicator for assessing the performance of an economy, especially to analyze the results of the process of economic development in a country or region in order to create a better economic growth, especially in developing countries in ASEAN. This study aimed to analyze the effect of population growth, unemployment and inflation to economic growth in four ASEAN countries in 2003 to 2013. By using a panel data analysis method to approach Fixed Effect Model (FEM). Result analysis concludes that there is significant influence between population growth and unemployment to economic growth in four ASEAN countries, while inflation showed no significant relationship to economic growth in the four ASEAN countries.